Development of Articulate Storyline 3-based learning media to improve students’ critical thinking and learning interest in junior high school statistics - Putri Puspita Sari; Anton Nasrullah; Sarah Caesarani; Mira Marlina; Silvia Ratnasari; Nguyen Tan Huynh (Universitas Sarjanawiyata Tamansiswa, 2025)
Statistics learning at the junior high school level requires students to develop critical thinking ability and learning interest; however, in practice, both aspects remain relatively low due to the dominance of conventional instruction and the limited use of interactive learning media. This study aims to develop interactive learning media based on Articulate Storyline 3 and to examine its validity, practicality, and effectiveness in improving students’ critical thinking ability and learning interest in junior high school statistics. The study employs a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects include 30 eighth-grade students divided into an experimental class and a control class. The research instruments comprise expert validation sheets, student response questionnaires, learning interest questionnaires, and critical thinking ability tests. The results indicate that the developed learning media demonstrate very high validity, excellent practicality, and effectiveness in enhancing students’ critical thinking ability and learning interest. Therefore, interactive learning media based on Articulate Storyline 3 are feasible as an innovative alternative for junior high school statistics learning. This study contributes to mathematics education by refining the integration of interactive digital media within statistics learning, offering an ADDIE-based development framework that informs future instructional design research while providing practical guidance for teachers in fostering student-centered learning and critical thinking.